Podstawy teologiczne kultu świętych w Kościele - Żądło, Andrzej (Studia Pastoralne, 2026)
The cult of saints creates a certain phenomenon that has been present for centuries in the life-mission of the Church. It is therefore worthy to devote adequate space for reflection of this theme, dedicated to its theological foundations. This theme in fact is continually timely and attracts our attention – both in life and research. The article presented above comes from statements relating to the conception and organization of Christian worship, from a previous attention to worship in the Old Testament, and which cult found its fulfillment in the New Covenant people, and so, in the life of Christ’s disciples upon the fulfillment of His work of salvation, brought to fulfillment at the coming of the Holy Spirit. Not surprisingly, and clearly emphasized by biblical texts, early Christians of ecclesial communities felt called to live holy lives on a daily basis, and sometimes even called each other „saints”. In fact, the Christians of that period not only felt a vocation to holiness, but witnessed their ability in practice. In addition, they were aware of the fact that such a calling does not guarantee any social prestige, but an obligation to follow Christ in His great devotion to the will of our heavenly Father – even to the Cross, which was taken up and carried freely, with the knowledge of the need of filling in their own flesh what is still lacking in regard to Christ’s afflictions, for the sake of His Body, which is the Church (Col 1:24). The demanding Christian life, namely the prospect of holiness lived out in the image of Jesus crucified and risen, caused the birth of a desire in the hearts of believers to memorialize – not only in the archives, but above all in the liturgy – the example left by Christians who throughout their lives could maturely answer the call to holiness addressed to them by God. In the examples of holiness that the Lord has instilled in their hearts, introduced in time into the liturgy, Christians began to discover – and are still discovering – the continuation of a plan holiness undertaken by God, constantly carried out in time according to the rhythms foreseen by Him. In venerating the saints, the Church proclaims the paschal mystery and gives glory to God for the work revealed in their lives, as well as recognizing in them witnesses, who have reached, through God’s multiple graces, eternal salvation – „They sing to God in heaven great glory and intercede for us” (SC 104).